The Success of Implementing and Spreading the Values of Pancasila Through Social Media Content in the Call to Clean the Environment by Pandawara Group - Oktaviani, Angelia; Aurelly, Ivanka Freisha; Aprilia, Luna Puji; Aprilia, Nadya Muli; Putri, Nida Amalia; Sanches, Unggul Mario Hizkia; Astawa, I Ketut (The Future of Education Journal, 2024)
Pandawara Group, a youth community based in Bandung, has become an inspiring example in efforts to promote cleanliness and environmental sustainability through the #onedayonetrashbag movement. This initiative encourages people to collect the trash they encounter daily and put it in one bag as a commitment to environmental cleanliness. In addition to focusing on concrete actions such as cleaning trash in various public areas, Pandawara Group also leverages the power of social media to spread positive messages about the importance of maintaining cleanliness and preserving nature. Through this movement, they not only encourage the public to actively participate but also voice the values of Pancasila, such as mutual cooperation (gotong royong), social justice, and humanity. Pandawara Group emphasizes the importance of collaboration in every activity, where each individual, from community members to the broader society, plays a role in maintaining cleanliness together. Their efforts are not limited to physical actions like trash cleaning, but also include education on proper waste management and environmental friendliness. Despite facing challenges, such as the lack of waste management facilities in some areas and difficulties in maintaining consistent public participation, this movement has succeeded in attracting the attention of various stakeholders, including the government, influencers, and other organizations, who together strive for cleanliness and environmental sustainability. By demonstrating that small collective actions can lead to significant impact, Pandawara Group provides a real example that collaborative efforts in environmental conservation can create positive and sustainable change.